2013
DOI: 10.2139/ssrn.2234277
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tax Knowledge and Budget Spending Influence on Tax Compliance

Abstract: We investigate within a controlled laboratory setting of a hypothetical tax system how tax knowledge about public expenditures and influence on budget spending affects tax compliance. To clearly disentangle any effects from factors that are known to influence tax compliance from previous studies, we control for tax commitment, risk attitude, income and effort exerted to earn the income which the taxpayers report truthfully or underreport to the tax authority. Non-parametric statistical analyses as well as mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…As in other similar studies (e.g., Djawadi and Fahr, 2013), we found that compliance is also sustained by increasing procedural justice. When participants have the opportunity of a direct participation into the rules of the tax system (they have voice on distribution), tax evasion is lower.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As in other similar studies (e.g., Djawadi and Fahr, 2013), we found that compliance is also sustained by increasing procedural justice. When participants have the opportunity of a direct participation into the rules of the tax system (they have voice on distribution), tax evasion is lower.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the mentioned studies, other works have recently contributed to understanding the impact of trust and knowledge on tax compliance by experimentally manipulating taxpayers' power in deciding about government budget spending (cf. Djawadi and Fahr, 2013;Abbiati, Antinyan and Corazzini, 2014;Lamberton, De Neve and Norton, 2014).…”
Section: Related Literaturementioning
confidence: 99%
“…Treatment 5 -National pride The evidence on the effectiveness of invoking national pride is mixed: there are examples where such messaging has been used successfully to increase tax compliance in the lab (Gangl et al, 2016;Macintyre et al, 2021); by contrast, in an experiment in Guatemala, the appeal to the taxpayers' national identity was less effective at increasing tax compliance than a social norms message and one framing noncompliance as a deliberate choice (Kettle et al, 2016). On the other hand, transparency about how tax revenue is spent can positively influence tax compliance (Djawadi and Fahr, 2013).…”
Section: Treatment 4 -Combined Guidance and Planning Promptmentioning
confidence: 99%
“…Provision of information on the uses and benefits of taxation thus increases tax compliance (Sussman and Olivola, 2011; Djawadi and Fahr, 2013). There is not much literature however on how feelings of empathy, triggered by the information provided on how taxpayers' money is spent on the less privileged, could be driving these higher compliance rates.…”
Section: Theoretical Framework and Derivation Of Hypothesesmentioning
confidence: 99%